Unveiling interactions of non-metallic inclusions within advanced ultra-high-strength steel: A spectro-microscopic determination and first-principles elucidation. (May 2021) - Singh, Harishchandra; Alatarvas, Tuomas; Kistanov, Andrey A; Aravindh, S Assa; Wang, Shubo; Zhu, Lin; Sarpi, Brice; Niu, Yuran; Zakharov, Alexei; de Groot, F.M.F.; Huttula, Marko; Cao, Wei; et al.
Abstract: Determining non-metallic inclusions (NMIs) are essential to engineer ultra-high-strength steel as they play decisive role on performance and critical to probe via conventional techniques. Herein, advanced Synchrotron X-ray absorption coupled with photoemission electron microscopy and first-principles calculations are employed to provide the structure, local bonding structure and electronic properties of several NMI model systems and their interaction mechanism within and the steel matrix. B K-, N K-, Ca L2, 3 - and Ti L2, 3 -edge spectra show that the additional B prefers to result in h-BN exhibiting strong interaction with Ca 2+ . Such Ca 2+ -based phases also stabilize through TiN, revealing the irregular coordination of Ca 2+ . Observed intriguing no interaction between TiN and BN is further supported with the first-principles calculations, wherein unfavorable combination of TiN and h-BN and stabilization of bigger sized Ca 2+ -based inclusions have been found. These observations can help to optimize the interaction mechanism among various inclusions as well as steel matrix. Graphical abstract: Image, graphical abstract